Ethical decision making and astute use of artificial intelligence - Masrek, Mohamad Noorman; Heriyanto, Heriyanto; Hussain, Abid (Edelweiss Applied Science and Technology, 2026)
This study examines the relationship between ethical decision-making and the astute use of artificial intelligence (AI) among university students in Malaysia. As AI becomes increasingly integrated into learning and future professional activities, understanding how ethical considerations shape AI usage is essential. Guided by Rest’s Four-Component Model of ethical decision-making and the Digital Intelligence framework, this research investigates whether students’ ethical reasoning influences their responsible engagement with AI tools. A survey was administered to university students using a structured questionnaire, and the data were analyzed through descriptive statistics and partial least squares structural equation modeling. The findings demonstrate a positive relationship between ethical decision-making and students’ astute use of AI, indicating that ethical awareness contributes meaningfully to how students interact with AI technologies. The study concludes that ethical competence plays a critical role in shaping students’ digital practices. These results offer important implications for educators, policymakers, and university administrators seeking to develop ethical guidelines, training modules, and institutional policies that promote responsible AI use in higher education and prepare students for ethical decision-making in AI-driven environments.